ANALISIS STRATEGI PEMASARAN PRODUK TABUNGAN EMAS PADA PT. PEGADAIAN (PERSERO) CABANG SUMBAWA BESAR - Jihan Faradila; K Kurniawansyah; Eko Sutrisno (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the Marketing Strategy of Gold Savings Products at PT Pegadaian (Persero) Sumbawa Branch. The type of this study was descriptive study with qualitative approach. The sources of data in this study were primary and secondary data. The type of data used in this study was qualitative data in the form of explanations from research informants regarding the strengths, weaknesses, opportunities and threats in the marketing environment of gold savings products at PT. Pegadaian (Persero) Sumbawa Branch. The numbers of informants in this study were 4 informants consisted of 1 key informant and 3 main informants. The tools used to collect data were observation, interviews, and documentation. The technique of analysis data in this study was SWOT analysis. Based on the results of the internal and external marketing environmental of gold savings products at PT. Pegadaian (Persero) Sumbawa Branch using SWOT analysis, it was determined that the marketing strategy for gold savings products at PT. Pegadaian (Persero) Sumbawa Branch was by Introducing the Potential of Price Increases in long time. Develop hybrid products that combine gold elements with investment instruments that can be freely traded. Reduce administration cost and storage by increasing operational efficiency. Offer physical gold products in the form of smaller coins or mini-bars.